Relationship between the concentrations of polychlorinated dibenzo- p-dioxins, polychlorinated dibenzofurans, and polychlorinated biphenyls in maternal blood and those in breast milk - Todaka, Takashi; Hirakawa, Hironori; Kajiwara, Jumboku; Hori, Tsuguhide; Tobiishi, Kazuhiro; Yasutake, Daisuke; Onozuka, Daisuke; Sasaki, Seiko; Miyashita, Chihiro; Yoshioka, Eiji; Yuasa, Motoyuki; Kishi, Reiko; et al. (Chemosphere (Oxford), 2010)
We measured the concentrations of polychlorinated dibenzo- p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), dioxin-like polychlorinated biphenyls (PCBs), and non-dioxin-like PCBs in paired samples of blood and breast milk collected from 89 primiparous mothers in Sapporo City, Japan, and studied the relationships of these compounds between blood and breast milk for these women plus 30 primiparous mothers in whom these data had been previously reported. The present study is one of the few studies in which the concentration distributions of PCDDs, PCDFs, dioxin-like PCBs, and non-dioxin-like PCBs have been investigated in blood and breast milk collected from the same mothers. The arithmetic mean TEQ concentrations of PCDDs, PCDFs, non- ortho PCBs, and mono- ortho PCBs in blood and breast milk of these 119 subjects were 8.2, 2.9, 5.1, and 0.4 pg TEQ g −1 lipid, respectively, and 4.8, 2.0, 4.0, and 0.4 pg TEQ g −1 lipid, respectively, with the total TEQ concentrations of these dioxin-like compounds being 7.0–36 (mean: 17, median: 14) and 5.7–41 (mean: 11, median: 10) pg TEQ g −1 lipid, respectively. The sums of the concentrations of 56 non-dioxin-like PCB congeners that were measured in the subjects’ blood and breast milk were 43–445 (mean: 120, median: 106) and 34–366 (mean: 90, median: 81) ng g −1 lipid, respectively, indicating that the total TEQ concentration and the total concentration of 56 non-dioxin-like PCB congeners in the maternal blood were notably higher than those in the breast milk. Statistically significant correlations were observed between maternal age and the total TEQ concentration of PCDDs, PCDFs, and dioxin-like PCBs or the total concentration of 56 non-dioxin-like PCB congeners in maternal blood, and significant correlations were also observed between maternal age and the total TEQ concentration of these dioxin-like compounds or the total concentration of 56 PCB congeners in breast milk. The total TEQ concentration of PCDDs, PCDFs, and dioxin-like PCBs in maternal blood showed a close correlation to that in subjects’ breast milk, and there was also good correlation between the total concentration of 56 non-dioxin-like PCB congeners in maternal blood and that in subjects’ breast milk. Pearson and Spearman correlation analyses showed a relationship between the total TEQ concentration of PCDDs, PCDFs, and dioxin-like PCBs and the total concentration of 56 non-dioxin-like PCB congeners in maternal blood, and also showed an association between the total TEQ concentration of these dioxin-like compounds and the total concentration of 56 PCB congeners in breast milk. The concentration of hexaCB-153 in maternal blood showed significant correlations to the total TEQ concentration of PCDDs, PCDFs, and dioxin-like PCBs or the total concentration of 56 non-dioxin-like PCBs in that sample. Moreover, the concentration of hexaCB-153 in breast milk also showed significant correlations to the total TEQ concentration of these dioxin-like compounds or the total concentration of 56 PCB congeners in that sample. These findings suggested that hexaCB-153 may be an indicator of total TEQ concentrations of PCDDs, PCDFs, and dioxin-like PCBs and total concentrations of 56 non-dioxin-like PCB congeners in blood and breast milk of primiparous mothers.